The traditional trade of Asia - Simkin, C. G. F (Oxford U.P, 1968)
Contents: The shaping of traditional trade; Townsmen and nomads,I; Medieval changes; Nomad havoc, 49; Mongolian conquests and their aftermath; The Khanates and the landways, 127; Intrusion, withdrawal, and disintegration; The passing of traditional trade...